FROG INTESTINAL PERFUSION TO EVALUATE DRUG PERMEABILITY: APPLICATION TO P-gp AND CYP3A4 SUBSTRATES - Neelima eYerasi; krishna edevarakonda; Himabindu evurimindi (Frontiers Media S.A., 2015)
AbstractTo evaluate the reliability of using in situ frog intestinal perfusion technique for permeability assessment of carrier transported drugs which are also substrates for CYP enzymes. Single Pass Intestinal Perfusion (SPIP) studies were performed in frogs of the species Rana tigrina using established method for rats with some modifications after inducing anesthesia. Effective permeability coefficient (Peff) of losartan and midazolam was calculated in the presence and absence of inhibitors using the parallel-tube model. Peff of losartan when perfused alone was found to be 0.427 ± 0.27×10-4cm/s and when it was co-perfused with inhibitors, significant change in Peff was observed. Peff of midazolam when perfused alone was found to be 2.03 ± 0.07 × 10-4cm/s and when it was co-perfused with inhibitors, no significant change in Peff was observed. Comparison of Peff calculated in frog with that of other available models and also humans suggested that the Peff values are comparable and reflected well with human intestinal permeability. It is possible to determine the Peff value for compounds which are dual substrates of P-gp and CYP3A4 using in situ frog intestinal perfusion technique. The calculated Peff values correlated well with reported Peff values of probe drugs. comparison of the Peff value of losartan obtained with that of reported human's Peff and Caco 2 cell data, and comparison of the Peff value of midazolam with that of reported rat's Peff, we could conclude that SPIP from model can be reliably used in preclinical studies for permeability estimation. This model may represent a valuable alternative to the low speed and high cost of conventional animal models (typically rodents) for the assessment of intestinal permeability.